Effectiveness of the Inquiry-Based Learning (IBL) Method on Eighth-Grade Students' Ability to Write Narrative Texts - Fitriyani, Anisa; Silvana, Ade; M, Deni (Research Horizon, 2023)
Inquiry-Based Learning (IBL) is a process that involves asking questions and finding answers to those questions. The aim of this research was to assess the effectiveness of the inquiry-based learning method on students' ability to write narrative texts. The research design employed for this study was pre-experimental. The target population consisted of eighth-grade students at MTS Tarbiyatul Banin Tanjung Belit. For the sample, all twenty-five eighth-grade students were included. Data collection was carried out using pre-test and post-test assessments. The collected data were analyzed using the Paired Sample T-Test. The results revealed that the obtained value of -57.511 was less than the critical value of -2.064, indicating a statistically significant positive effect on students' ability to write narrative texts. This improvement was observed when using the Inquiry-Based Learning (IBL) method among the eighth-grade students at MTS Tarbiyatul Banin Tanjung Belit."